UJI AKTIVITAS ANTIOKSIDAN EKSTRAK BIJI PEPAYA DENGAN PELARUT METANOL MENGGUNAKAN METODE 2,2- DIPHENYL 1-PICRILHIDRAZYL (DPPH) - Alfin Surya; Zaiyar Zaiyar; Rosa Murwindra (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2023)
Papaya (Carica papaya L) is a popular plant in tropical regions such as as Indoneisa. whole areas of papaya from the root to the tio of the leaf, including the flower, fruits and seeds have good health benefits. Most studies see only the beneficial effects of the fruit and leaves, since they treat papaya seeds as waste have and are of no benefit. Papaya seeds are used as traditional remedies such as treating diarrheal diseases, skin diseases. Papaya seeds as an antibacterial that can kill bacteria by damaging the integrity of bacterial cells membranes. The papaya seeds are thought to contain a high level metabolic compound such a flavonoids, tokoferols, a terponoids that works as antioxidal in free radical counteract. Antiodants are substances that have small molecular weights that impede the oxidation reaction by promoting free radicals and highly reactive molecules that cause resistance cell damage. The study aims to determine the antioxidant activity on the extract of papaya seeds by using methanol by method of 2.2- diphenyl 1- picrylhidrazyl (DPPH). Research has shown that extract of papay methanol has IC50 of 872,0964 ppm indicates the antioxidal activity in papaya seed extract is very weak.